Context Dependency in Bark Beetle-Fungus Mutualisms Revisited: Assessing Potential Shifts in Interaction Outcomes Against Varied Genetic, Ecological, and Evolutionary Backgrounds - Six, Diana L.; Klepzig, Kier D. (Frontiers in Microbiology, 2021)
Context dependency occurs when biological interactions shift in sign or magnitude depending upon genetic, abiotic, and biotic context. Most models of mutualism address systems where interaction outcomes slide along a mutualism-antagonism continuum as environmental conditions vary altering cost-benefit relationships. However, these models do not apply to the many mutualisms that involve by-product benefits and others that do not have antagonistic alternate states. The ubiquity of such mutualisms indicates a need for different approaches and models to understand how environmental variability influences their strength, stability, and ecological roles. In this paper, we apply the concept of context dependency to mutualisms among bark beetles and fungi that span a variety of life strategies and exposures to environmental variability. Bark beetles and their mutualist fungi co-construct a niche based on by-product benefits that allows them to exist in a resource that is otherwise intractable or inaccessible. For the closest of these partnerships, this has resulted in some of the most influential agents of forest mortality in conifer forests worldwide. Understanding these symbioses is key to understanding their influence on forest structure and dynamics and responses to change. We found no evidence that bark beetle mutualisms change in sign as conditions vary, only in magnitude, and that the ‘closest’ (and most environmentally influential) of these partnerships have evolved behaviors and mechanisms to reduce context-dependency and stabilize benefit delivery. The bark beetle-fungus symbioses most likely to slide along a mutualism-antagonism continuum are those involving loosely associated facultative symbionts that may provide benefits under some circumstances and that are horizontally transmitted by the beetle host. Additionally, some symbiotic fungi are never mutualists – these ‘third party’ fungi are exploiters and may shift from commensalism to antagonism depending on environmental context. Our assessment indicates that a careful differentiation between bark beetle-fungus partnerships is crucial to understanding how they influence forests and respond to environmental variability.